Professores que atuam na EJA: entre a formação e a prática docente - SILVA, Carla Ivana Amorim da (2021)
This research refers to the training of teachers who work in EJA and the implications of this training in the practice of these teachers. It is linked to the research group “Escola, Currículo e Formação Docente” (“School, Curriculum and Teacher Training”) at the Federal University of Maranhão and its general objective is to analyze the training of teachers who work in EJA in the Municipal Education Network of São Luís and the implications for teaching practice. In carrying out the research, a qualitative approach was adopted, using instruments and techniques from bibliographic and documentary research, semi-structured interviews and a questionnaire. The qualitative approach makes it possible to work with the universe of meanings, motives, aspirations, beliefs, values and attitudes, which corresponds to a deeper space of relationships, processes and phenomena that cannot be reduced to the operationalization of variables. It favored the analysis and interpretation of the collected data, taking into account the categories dealt with in this research and the subcategories arising from the researched object itself. The research was carried out in a school in the municipal education network in São Luís and had four subjects: three teachers, and a pedagogical coordinator of the management team. Among the authors who supported us, the following stand out: Paulo Freire(1987, 1995, 1996, 2006 ); Vanilda Paiva(1987 ); Bernadette Gatti (2019); Demerval Saviani (2008, 2009); Claudia Borges Costa and Maria Margarida Machado (2010); Miguel G. Arroyo(2006); Júlio Diniz-Pereira(2001); Maurice Tardif(2005); Selma Garrido Pimenta(1997, 2017); Silvio Sánchez Gamboa (1998 ) Minayo (1994), among others. The research results pointed out the need to offer specific training on EJA for teachers who work in this type of teaching, as well as the need for the Municipal Department of Education to establish criteria for the admission of teachers into the teaching network, which take into account the training of teachers, supported by theoretical and practical foundations, in order to ensure a coherent performance with a human training project aimed at this segment. As for the professors who are already working at EJA, the continuing education actions must be guided by the needs presented by the professors, in a way that significantly contributes to the teaching practice.